Thermodynamic, kinetic and solid-state study of divalent metal complexes of 1,4,8,11-tetraazacyclotetradecane (cyclam) bearing two trans (1,8-)methylphosphonic acid pendant arms - Svobodová, Ivona; Lubal, Premysl; Plutnar, Jan; Havlícková, Jana; Kotek, Jan; Hermann, Petr; Lukes, Ivan (Dalton transactions : an international journal of inorganic chemistry, 2006)
Divalent metal complexes of macrocyclic ligand 1,4,8,11-tetraazacyclotetradecane-1,8-bis(methylphosphonic acid)) (1,8-H4te2p, H4L) were investigated in solution and in the solid state. The majority of transition-metal ions form thermodynamically very stable complexes as a consequence of high affinity for the nitrogen atoms of the ring. On the other hand, complexes with Mn2+, Pb2+ and alkaline earth ions interacting mainly with phosphonate oxygen atoms are much weaker than those of transition-metal ions and are formed only at higher pH. The same tendency is seen in the solid state. Zinc(II) ion in the octahedral trans-O,O-[Zn(H2L)] complex is fully encapsulated within the macrocycle (N4O2 coordination mode with protonated phosphonate oxygen atoms). The polymeric {[Pb(H2L)(H2O)2].6H2O}n complex has double-protonated secondary amino groups and the central atom is bound only to the phosphonate oxygen atoms. The phosphonate moieties bridge lead atoms creating a 3D-polymeric network. The [{(H2O)5Mn}2(micro-H2L)](H2L).21H2O complex contains two pentaaquamanganese(II) moieties bridged by a ligand molecule protonated on two nitrogen atoms. In the complex cation, oxygen atoms of the phosphonate groups on the opposite sites of the ring occupy one coordination site of each metal ion. The second ligand molecule is diprotonated and balances the positive charge of the complex cation. Complexation of zinc(II) and cadmium(II) by the ligand shows large differences in reactivity of differently protonated ligand species similarly to other cyclam-like complexes. Acid-assisted dissociations of metal(II) complexes occur predominantly through triprotonated species [M(H3L)]+ and take place at pH < 5 (Zn2+) and pH < 6 (Cd2+).